2012
DOI: 10.1186/1479-5876-10-194
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19V DNA contamination in Chinese plasma and plasma derivatives

Abstract: BackgroundTo ensure the safety of plasma derivatives, screening for human parvovirus B19V genomic DNA in donated plasma using a pooling strategy is performed in some countries. We investigated the prevalence of B19V DNA and anti-B19V antibodies in Chinese plasma pools, plasma derivatives and plasma donations to evaluate the risk posed by B19V.MethodsUsing a Q-PCR assay developed in-house, we tested for B19V genomic DNA in 142 plasma pools collected between January 2009 and June 2011 from two Chinese blood prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
11
3
3
Order By: Relevance
“…Our prevalence data in WB donors was significantly lower than the prevalence reported by Ke et al () (0·58%), by Wang et al () (2·67%) and by Yu et al () (6·80%). In addition, we found two minipools (including 96 individual source plasma donations) positive for B19V DNA (3·77%, 2/53) which was significantly lower than that reported by Zhang et al () in which most minipools (including 90 individual source plasma donations) were contaminated with B19V DNA (97%, 536/552). This surprising difference may be due to three factors.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Our prevalence data in WB donors was significantly lower than the prevalence reported by Ke et al () (0·58%), by Wang et al () (2·67%) and by Yu et al () (6·80%). In addition, we found two minipools (including 96 individual source plasma donations) positive for B19V DNA (3·77%, 2/53) which was significantly lower than that reported by Zhang et al () in which most minipools (including 90 individual source plasma donations) were contaminated with B19V DNA (97%, 536/552). This surprising difference may be due to three factors.…”
Section: Discussioncontrasting
confidence: 80%
“…In our study, the samples were collected from the donors in Sichuan province which is located in the southwest of China. It is known that winter and spring are the epidemic periods of respiratory virus in this area (Zhang et al , ). However, the donations of our study were collected from July to December in 2013 which was not the epidemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples screened in this study consisted of 6096 individual plasma samples collected from one Chinese blood product manufacturer between October 2012 and September 2013 (October 2012, 893 samples; November 2012, 90; December 2012, 714; January 2013, 719; February 2013, 711; March 2013, 630; April 2013, 90; May 2013, 630; June 2013, 449; July 2013, 450; August 2013, 360; September 2013, 360), 241 plasma pools, and 326 batches of blood products (including 65 batches of albumin, 197 batches of intravenous immunoglobulin [IVIG], 47 batches of anti‐hemophilic Factor VIII [FVIII], 12 batches of fibrinogen, and five batches of prothrombin complex concentrate [PCC]) that had been collected in our laboratory during 2010 to 2012. All the samples tested negative for routine pathogens according to standards established by the Chinese Ministry of Health (routine pathogens were tested by the blood product manufacturers) …”
Section: Methodsmentioning
confidence: 99%
“…Several inactivation procedures are available but some of them are recognized to be less effective on non-enveloped viruses, such as human parvovirus B19 (B19 V), Hepatitis A (HAV) or Hepatitis E (HEV) viruses [2]. Moreover, recent publications have also confirmed that some viral reduction methods (solvent/detergent and heat treatment) are inadequate to inactivate high viremic titers of these viruses in plasma pools or derivates [3,4]. Given this, the threat for blood safety due to emerging viruses is of crucial importance.…”
Section: Introductionmentioning
confidence: 99%